Fragments of Everyday Life and Art: An Interview with Hortência Moreira (Revista de Ensino em Artes, Moda e Design, 2026)
The interview with visual artist and architect Hortência Moreira reveals a trajectory deeply connected to artistic practice since childhood. Hortência shares how she grew up in a creative environment, within her mother’s sewing studio. Throughout the conversation, she reflects on the organic way in which art became intertwined with her personal and professional life, from her earliest drawings and experiments, and her specialization in the field of art, to her consolidation as an artist within the visual arts circuit. She recounts her experiences with competitions, group exhibitions, art salons, and her first solo exhibition, highlighting a continuous path marked by commitment to artistic language. Beyond her professional trajectory, the interview reveals the maturation of an artist who has always been in motion, seeking spaces for creation, research, and engagement within the cultural landscape. This artist was selected to accompany the three 2026 dossiers of the Journal of Teaching in Arts, Fashion and Design, with this being the first published interview, focusing on her formative trajectory. Works by Hortência Moreira were chosen to compose each of the covers of the issues published this year.
Keywords: art; architecture; aesthetic experiences